Relationship between particular matter (PM10) air pollution with disease and lung function among schoolchildren residing near cement factory, 1998 - Zainol Ariffin Mohammed; Dayang Aminah Ali (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross-sectional study was done in two different areas to assess the association between air pollution with respirable dust (PMI0) and respiratory health of primary school children, which was held in September 1998. The study was done in two areas of different air quality status, i e, Kampong Tasek, Ipoh which is located within a 2 km radius from cement factory, while the other area is Kampong Ayer Puteh, located nearly 80 km north of Ipoh. The aim of the study is to assess the relationship between air pollution by respirable dust (PMIO), and respiratory health of primary schoolchildren living in both areas. Respiratory symptoms were assessed with a guided questionnaire while pulmonary functions were measured with a 'Pony" spirometry. Respirable dust was measured with a portable 'MiniVol' air sampler, at 4 locations in each study area. Prevalence of acute respiratory symptoms was high, around 30 % and forced expiratory volume in I second (FEVI) was lower among children from Kampong Tasek. An association between prevalence of respiratory symptoms especially coughs and levels of PMIO were derived and there was a significant difference between both areas. Children in Kampong Tasek were also detected to have significantly high prevalence of eye and skin diseases. Although there was no different of forced vital capacity (FVC) observed, but there were significance differences of FEVI compared to both assessed areas. In conclusion, air pollution caused by respirable dust (PM10) is associated with increase in respiratory symptoms and reduced FEVI of primary school children.